Ecology and Cıtızenshıp; Buıldıng Student’s Eco Cıtızenshıp Throughengagıng The ‘Green Youth’ Communıty Wonosalam Jombang - Akhwani, Akhwani (Universitas Nahdatul Ulama Surabaya, 2020)
This study intends to describe the involvement of students in community activities of “Green Youth” to maintain environmental sustainability in building eco-citizenship of students who care for their environment. This research uses descriptive qualitative method. Data collection techniques include interviews, observation and documentation. The informants in this study were three people from the green youth community as well as several students who took part in environmental preservation activities. The results of this study indicate the activities that students participate in in the green youth community include: (1) Implementation of the habit of disposing of garbage in its place; (2) River patrol activities; (3) Creating a slogan; (4) Treatment of springs; and (5) Tree planting. Through involvement in this group is because they want to create a good environment and can provide awareness (reflection) of the need to care for the environment. The end result is that the activities carried out have been able to build the spirit of students with eco-citizenship where awareness of the environment is built with evidence of maintaining maintained barren forests that have grown around five to six meters of trees and where a spring has been installed a useful wall that makes water easier